Directed panspermia: a 21st century perspective. (1st May 2017) - Sleator, Roy; Smith, Niall
Applying 21st century technology to the design and development of a hypothetical extra-terrestrial colonisation programme, we reimagine 'directed panspermia' from the perspective of Crick and Orgel's 'technological society', 44 years after the publication of their original landmark paper.